Geospatial Education as a Means of Improving the Skills of Geography Teachers - Abikbayev, Yerzhan; Laiskhanov, Shakhislam; Seminar, Erkegul; Nurmagambetuly, Zhanbolat; Assen, Nurdana; Taukebayev, Omirzhan; Kopbossyn, Amandyk (Faculty of Geography, Universitas Gadjah Mada, 2025)
In the context of digitalization, there are many obstacles to the successful introduction of geospatial technologies (GST) into school geography and their integration with geographical education. The main one is the low geospatial education of teachers. The purpose of this study is to develop a curriculum for advanced training courses and an experimental study of its effectiveness by analyzing the content of the school's geography educational programs and studying the demands of geography teachers for geospatial knowledge. During the study, such general scientific methods as review, analysis, synthesis of scientific papers, study, comparison of regulatory documents on education were used. Based on the analysis of the role of GST in the curricula of Kazakhstan's secondary education and a survey study of the professional needs of geography teachers in geospatial education, 2-level (basic, advanced) training programs of advanced training courses for geography teachers, an additional manual for it, have been developed. The effectiveness of the basic level curriculum has been proven by an experimental study. The results of